GENDER DIFFERENCES IN INVESTMENT DECISIONS UNDER LOSS LIMITATION - Peliova, Jana (European Scientific Journal, ESJ, 2014)
In our study we focus on the impact of loss limitation on risk attitudes of men and women. We conducted laboratory experiment on risk taking under limited losses. Our results support the outcomes of large scale surveys, whose results shown significant difference in risk taking among genders. Our empirical results show the difference in risk taking decisions on both, unregulated market as well as on regulated markets. Male subject were investing more than female subjects, as predicted. An interesting outcome is that female subjects did not reflect the change in market settings into the change in their decisions. Male subjects increased their wagers in regulated market settings.